PERAN LOYALITAS TENAGA PEMASARAN DAN PRESTASI KERJA TERHADAP KINERJA TENAGA PEMASARAN MELALUI MOTIVASI KERJA PADA PT QUADRA INTI SOLUSI - Suharyon, Suharyon; Mukhlis, Ahmad; Permana, Angrian (Unitri Press, 2024)
The objective of this study is to develop a model for marketing staff performance by considering motivation as a mediating variable. The research methodology employed includes a survey conducted among 333 employees of PT Quadra Inti Solusi, with a sample size of 77 respondents. The findings reveal the following: 1) there is no significant impact of marketing staff loyalty on marketing staff performance; 2) social interaction positively influences marketing staff performance; 3) marketing staff loyalty does not significantly affect motivation; 4) work performance has a positive effect on motivation; 5) motivation significantly impacts marketing staff performance; 6) marketing staff loyalty does not influence marketing staff performance through motivation; and 7) work performance positively affects marketing staff performance through motivation.. Conclusion, to improve marketing staff performance, encouragement from leaders and colleagues is needed, and it is important to give awards for employee achievements.